GRAYSCALE IMAGE WATERMARK DETECTION - Kaur, Randeep; Dhillon, Kamaljit Kaur (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
A Digital watermarking is a technique that provides a solution to the longstanding problems faced with copyrighting digital data. Digital watermarks are pieces of information added to digital data (audio, video, or still images) that can be detected or extracted later to make an assertion about the data. This information can be textual data about the author, its copyright, etc; or it can be an image itself. Watermarking Based on DCT Coefficient Modulation technique embeds the watermark in the DCT domain to increase the robustness of the watermarking scheme.DCT based watermarking is an example of frequency domain watermarking. The objective of this research work is to implement DCT based watermarking technique on gray scale image. The study focuses on evaluating the robustness of watermarked image after having three different attacks on watermarked image and extraction of watermark from that particular image. To compare the DCT based watermarking with LSB based watermarking and to validate the proposed work & the comparative results of watermarking using DCT and LSB are also presented. This paper recommends DCT based technique for achieving robustness in digital image watermarking.